RESULTS OF STUDY PERIODONTAL TISSUE CONDITION UNDER GLASS SPLINTING OF TEETH - N.P. Chuev; L.D. Chulak; Y.V. Gryzodub (Ukrainian Medical Stomatological Academy, 2015)
Purpose: comparative clinical assessment of oral tissues in prosthetics with ceramic constructions in the complete absence of the tooth crown. Methods: For improving methods of non-metal prosthesis the complete destruction of the tooth crown, we have developed method of manufacturing non-metal inlay. This technique has same differs from traditional technology..The stove and activate the automatic compression program. To increase the strength of ceramic inlay used "fast" cooling without slow cooling in the furnace. Given that the bond strength zirconia undyed white with facing materials was significantly compared to colored zirconia inlay staining was performed. Fixing in the oral cavity was carried out with a universal two-component adhesive system Totalcem ("Itena", France). Restoration covered the water-soluble glycerin to prevent the formation of oxygenated layer photopolymer lamp illuminates. The first group (control), we included patients who have ceramic crowns under the inlays are not prepared - if necessary, restored photopolymer materials or glass ionomer cement. The second group included patients who had prosthesis single dentition defects such as ceramic structures using metal inlays made of Cobalt alloy. The third group consisted of patients who had prosthesis destroyed crown part of teeth using ceramic inlays made under the Protocol providing dental care. The fourth group, we selected patients whose prosthesis was performed according to our scheme and our proposed restoration designs of ceramic inlays. Conducted studies of leukocyte migration to mucosal prosthetic area. The sample reflects the state of the oral mucosa and to evaluate the degree of migration of white blood cells and epithelial cells desquamated into the oral cavity. The sample studied in the modification of Sukmanskiy using the cameras Fucks - Rosenthal. Number of leukocytes and epithelial cells was determined in 1 ml of mouth wash. Results: Prosthodontics treatment of control group (during the restoration of the photopolymer inlay) intensity of the emigration of leukocytes in 2 months has not changed much, but 1 month after prosthetic increased due adaptation to the artificial crown. Similar changes took place in the second group of studies (using Cobalt alloy inlais). In the third group showed a clear decrease in leukocyte migration (up to 385.5 thousands / 1 ml), indicating a decrease in the intensity of chronic inflammatory processes occurring in the lining of the periodontal tissues in prosthetics ceramic inlays. At 1 year after fixation of the prosthesis, these figures decreased by more than 15%. In the group of patients which are made of ceramic inlays of our technology, the tendency to reduce the intensity of leukocyte migration by 18.9 % to (465,5 ± 42,5) to (377,6 ± 38,2) thousands. Cells after 1 month after the prosthesis. At 1 year after prosthesis index has decreased by 3.3%. In the control group there is a constant, unchanging rate of epithelial desquamation. In the second group (using a metal inlais) the rate of shedding at the time of manufacture of the coating structure - ceramic crowns shedding increased intensity - up to 49,4 ± 0,6 thous. cells / 1 ml.. This fact is attributed to the reaction of periodontal tissue on the metal inlay and the process of prosthetics. In the long-term period the intensity of shedding of cells is somewhat reduced - up to 38,2 ± 2,8 thous. cells / 1 ml., but still 12.8% higher than the level before the prosthesis, which indicates, in our opinion, on the migration of metal oxides, which is produced in the gingival pocket in periapical tissue, which causes its irritation. In the study of the intensity of epithelial desquamation in the third group (the use of ceramic inlays and ceramic crowns) fluctuations of the epithelial desquamation are minimal. A similar situation is observed in patients of the fourth group. Conclusions: In the group of patients which are made of ceramic inlays of our technology, the tendency to reduce the intensity of leukocyte migration by 18.9%. Cells after 1 month after the prosthesis. At 1 year after prosthesis index has decreased by 3.3%.